Phytochemicals as Potent Modulators of Autophagy for Cancer Therapy - Echeverria-Morgado, J (Elsevier Ireland Ltd, 2018)
The dysregulation of autophagy is involved in the pathogenesis of a broad range of diseases, and accordingly universal research efforts have focused on exploring novel compounds with autophagy-modulating properties. While a number of synthetic autophagy modulators have been identified as promising cancer therapy candidates, autophagy-modulating phytochemicals have also attracted attention as potential treatments with minimal side effects. In this review, we firstly highlight the importance of autophagy and its relevance in the pathogenesis and treatment of cancer. Subsequently, we present the data on common phytochemicals and their mechanism of action as autophagy modulators. Finally, we discuss the challenges associated with harnessing the autophagic potential of phytochemicals for cancer therapy. © 2018 Elsevier B.V.